2016
DOI: 10.1155/2016/6538192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravitreal Ranibizumab Injection on Chinese Patients with Wet Age-Related Macular Degeneration: 5-Year Follow-Up Results

Abstract: Purpose. To observe the effect of intravitreal ranibizumab injection on wet age-related macular degeneration (wAMD) over 5 years in Chinese patients. Methods. Thirty-seven patients who were diagnosed with wAMD in our hospital from June 2007 to June 2014 were retrospectively reviewed. The PRN regimen and the treatment and extend regimen were applied. Best corrected visual acuity (BCVA), number of ranibizumab injections, and changes in the choroidal neovascularization (CNV) lesion over 5 years were analyzed. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Subretinal fibrosis and atrophy in the outer layer of the retina were also reported to be the main pathological cause of visual loss at the end of wAMD. 6 Although fibrosis is a repair reaction of tissue damage, CNV can also develop fibrosis in the natural course of the disease. Studies have shown that anti-VEGF treatment can change the balance between connective tissue growth factor (CTGF) and VEGF, increase the ratio of CTGF/VEGF, and induce angiogenesis to change to fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Subretinal fibrosis and atrophy in the outer layer of the retina were also reported to be the main pathological cause of visual loss at the end of wAMD. 6 Although fibrosis is a repair reaction of tissue damage, CNV can also develop fibrosis in the natural course of the disease. Studies have shown that anti-VEGF treatment can change the balance between connective tissue growth factor (CTGF) and VEGF, increase the ratio of CTGF/VEGF, and induce angiogenesis to change to fibrosis.…”
Section: Introductionmentioning
confidence: 99%